Spatial and temporal aspects of irrigation water quality in South Bug and Kamianska irrigation systems - Chornyy, S. G.; Isayeva, V. V. (AgroChemistry and Soil Science, 2022)
Much of Ukraine is located in areas of insufficient moisture, and therefore the food supply and export potential of the state largely depends on the availability, condition and efficiency of irrigated land use. A factor that significantly affects the development of irrigation in the South of Ukraine is the quality of irrigation water. The aim of the article is to highlight the results of the study of spatial-temporal aspects of various indicators of agronomic quality of irrigation waters of the South Bug Irrigation System (SBIS) and Kamianska Irrigation System (KIS). The task of the research was to determine the degree of danger of salinization of soils, the hazard of physical degradation of soils, the danger of toxic effects on the plant of certain toxic anions and cations and the pH value. In terms of the risk of soil salinization, these waters have a medium level of hazard. Such irrigation water has certain limitations in use. If there is no noticeable reduction in the yield of the main crops at the SBIS, then watering with this water will lead to a noticeable loss of yield at the KIS for the most sensitive to salinity crops. KIS and SBIS irrigation water have medium risks of potential salinization of soils, which makes the application of gypsum a mandatory technological measure in the process of growing crops. Regarding the impact of sodium cations on agricultural plants, the quality of irrigation water on the lands of SBIS is low and medium, and on the lands of KIS – average. But at the end of the irrigation season under the influence of temperature and probable inflow into reservoirs along the route of transportation of mineralized groundwater, the use of such water on KIS lands requires significant restrictions due to the high risk of injury to plants with excess sodium cations. The low initial content of chlorine anions in the Southern Bug River, which does not change significantly in the process of water transportation, does not lead to toxic effects on plants in all lands of both irrigation systems hydrocarbonates dominate among all anions in irrigation water, both on SBIS and on KIS, but the content of bicarbonates does not exceed the normative indicators inherent in "average danger of influence on soil solution". At the same time, the presence of large relative amounts of hydrocarbonate anions and sodium cations leads to high values of the "residual sodium carbonate index" (RSCI), especially in the KIS, which indicates the potential danger of rising sodium in water, which can have negative consequences for soil and for the plant. The pH values of irrigation water on the entire transport route in all terms of measurement often fall into the range of values acceptable for agricultural plants. Thus, the assessment of water used in SBIS and KIS, for most parameters shows an average and low agronomic quality, and therefore only limited use of this water for irrigation is possible. This is especially true of KIS lands.